Uric acid and neurological disease: a narrative review - Otani, Naoyuki; Hoshiyama, Eisei; Ouchi, Motoshi; Takekawa, Hidehiro; Suzuki, Keisuke (Frontiers in Neurology, 2023)
Hyperuricemia often accompanies hypertension, diabetes, dyslipidemia, metabolic syndrome, and chronic renal disease; it is also closely related to cardiovascular disease. Moreover, several epidemiological studies have linked hyperuricemia and ischemic stroke. However, uric acid may also have neuroprotective effects because of its antioxidant properties. An association between low uric acid levels and neurodegenerative diseases has been suggested, which may be attributed to diminished neuroprotective effects as a result of reduced uric acid. This review will focus on the relationship between uric acid and various neurological diseases including stroke, neuroimmune diseases, and neurodegenerative diseases. When considering both the risk and pathogenesis of neurological diseases, it is important to consider the conflicting dual nature of uric acid as both a vascular risk factor and a neuroprotective factor. This dual nature of uric acid is important because it may help to elucidate the biological role of uric acid in various neurological diseases and provide new insights into the etiology and treatment of these diseases.